Co-delivery of antigen and dual agonists by programmed mannose-targeted cationic lipid-hybrid polymersomes for enhanced vaccination. (June 2019) - Zhu, Dunwan; Hu, Chunyan; Fan, Fan; Qin, Yu; Huang, Chenlu; Zhang, Zhiming; Lu, Lu; Wang, Hai; Sun, Hongfan; Leng, Xigang; Wang, Chun; Kong, Deling; et al.
Abstract: Exploiting Toll-like receptor (TLR) agonists or their certain combinations can enhance the immune potency of subunit vaccine. Nevertheless, the design of co-delivery systems which can act in a synergistic and spatio-temporal way to achieve effective and durable specific immune response is still challenging. Here we fabricated mannose-functionalized lipid-hybrid polymersomes (MAN-IMO-PS) for co-delivery of ovalbumin antigen both inside the inner core and outside the lipid layer, TLR7/8 agonist imiquimod within the hydrophobic membrane, TLR4 agonist monophosphoryl lipid A in the lipid layer as programmed nanovaccine to synergistically activate immune responses for improving vaccine efficacy. After efficiently internalized by dendritic cells via mannose targeting and TLR4 ligating, MAN-IMO-PS significantly enhanced cross-presentation and cytokine production. In addition, MAN-IMO-PS showed depot effect at the injection site and enhanced migration to draining lymph nodes. Mice immunized with MAN-IMO-PS elicited greater lymphocyte activation, CD4 + and CD8 + T cell response, effector cytokines secretion, and induced Th-1 biased humoral responses. More importantly, prophylactic vaccination by MAN-IMO-PS significantly delayed tumor occurrence, suppressed tumor growth with prolonged survival, and achieved long-term immune effect. The present study demonstrates a rationally designed nanovaccine for combining antigen, different TLR agonists, and targeting moiety in a programmed manner to induce synergistic antitumor immune response.